Effect of expanded dulaglutide weekly doses (3.0 mg and 4.5 mg) on cardiovascular disease risk factors in participants with type 2 diabetes at increased cardiovascular disease risk: a post hoc analysis of the AWARD‐11 study. Issue 9 (29th May 2022) - Cox, David A.; Wang, Hui; Nicolay, Claudia; Bethel, Mary Angelyn
Abstract: Aims: This post hoc analysis investigated the effect of dulaglutide on cardiovascular disease (CVD) risk factors in subgroups of participants at increased CVD risk in the AWARD‐11 study. Methods: Participants who received once weekly dulaglutide 1.5, 3.0 or 4.5 mg for 52 weeks were categorized according to their baseline Framingham CVD risk category [low (N = 295), medium (N = 481) and high (N = 1054) risk], as well as their baseline CVD risk according to the REWIND study eligibility criteria (N = 953). Serum lipids and vital signs were assessed at baseline and at 52 weeks. Data were analysed as least squares mean percentage change from baseline for lipids and least squares mean change from baseline for vital signs. Results: Demographic and baseline clinical characteristics were balanced across doses within the CVD risk groups. In the high Framingham CVD risk and REWIND‐like groups, dulaglutide resulted in dose‐related decreases in total cholesterol (≤6.0%), non‐high‐density lipoprotein cholesterol (≤8.8%), very‐low‐density lipoprotein cholesterol (≤19.4%) and triglycerides (≤21.5%), with little change in low‐density lipoprotein cholesterol and high‐density lipoprotein cholesterol. Systolic and diastolic blood pressure decreased up to 5.6 mmHg and 1.6 mmHg, respectively, and heart rate increased up to 2 beats/min. Conclusions: This post hoc analysis suggests the magnitude of the favourable effects of dulaglutide 3.0 mg and 4.5 mg on several cardiometabolic CVD risk factors was similar to, if not greater than, those of dulaglutide 1.5 mg among participants with type 2 diabetes and increased CVD risk. ClinicalTrials.gov Identifier: NCT03495102.